Population Genomics Reveals Elevated Inbreeding and Accumulation of Deleterious Mutations in White Raccoon Dogs - Yinping Tian; Yu Lin; Yue Ma; Jiayi Li; Sunil Kumar Sahu; Jiale Fan; Chen Lin; Zhiang Li; Minhui Shi; Fengping He; Lianduo Bai; Yuan Fu; et al. (Biology)
The formation of animal breeds usually begins with a small subsample from their ancestral population. Deleterious mutations accumulate in the population under genetic drift, inbreeding, and artificial selection during the development and maintenance of traits desired by humans. White raccoon dogs are among the most popular breeds of farmed raccoon dogs, but white raccoon dogs are more susceptible to disease and have a lower reproductive ability. However, the accumulation of deleterious mutations in this white breed is largely unknown. By analyzing and comparing whole-genome sequencing data from 20 white raccoon dogs and 38 normal raccoon dogs, we detected an increased occurrence of loss-of-function (LoF) mutations in white raccoon dogs compared with normal raccoon dogs. With the finding of a significantly higher dosage of homozygous missense mutations in the white raccoon dog genome, we detected a greater fitness cost in white raccoon dogs. Although a much higher FROH level for ROH fragments longer than 1 Mb has been reported in white raccoon dogs, we did not detect a genetic signal of genetic purging in white raccoon dogs. This study provides valuable genomic resources and new insights into the accumulation of mutation loads in farmed raccoon dogs.